Subtle side chain modification of triphenylamine‐based polymer hole‐transport layer materials produces efficient and stable inverted perovskite solar cells. Issue 2 (12th April 2022) - Xie, Yue‐Min; Yao, Qin; Xue, Qifan; Zeng, Zixin; Niu, Tianqi; Zhou, Yingzhi; Zhuo, Ming‐Peng; Tsang, Sai‐Wing; Yip, Hin‐Lap; Cao, Yong
Abstract: Polymer hole‐transport layers (HTLs) are critical components of inverted perovskite solar cells (IPVSCs). Triphenylamine derivatives PTAA (poly[bis(4‐phenyl)(2, 4, 6‐trimethylphenyl)amine]) and Poly‐TPD (poly[ N, N ′‐bis(4‐butylphenyl)‐ N, N ′‐bis(phenyl)benzidine]) have been widely adopted as hole‐transport materials due to their perovskite passivation effects and suitable energy levels. However, the passivation mechanism (i.e., the functional group responsible for perovskite passivation) of triphenylamine derivative polymers remains unclear, hindering the development and application of this polymer type. Here, we develop a novel Poly‐TPD derivative, S‐Poly‐TPD, by replacing the n‐ butyl functional group of Poly‐TPD with an isobutyl group to explore the influence of alkyl groups on HTL performance and top‐deposited perovskite properties. Compared with Poly‐TPD, the increased CH3 ‐terminal unit density and the decreased spatial distance between the –CH–CH3 and –CH2 –CH3 units and the benzene ring in S‐Poly‐TPD not only enhanced the hole‐transport ability but also improved the perovskite passivation effect, revealing for the first time the role of the alkyl groups in perovskite passivation. As a result, the S‐Poly‐TPD‐based IPVSCs demonstrated high power‐conversion efficiencies of 15.1% and 21.3% in wide‐bandgap [MAPbI2 Br(SCN)0.12 ] and normal‐bandgap [(FAPbI3 )0.92 (MAPbBr3 )0.08 ] devices, respectively. Abstract : A novel S‐Poly‐TPD HTL was developed by replacing the n‐ butyl functional group in Poly‐TPD with an isobutyl group, which not only improves intermolecular stacking to enhance hole mobility but also reveals the role of the alkyl group in the HTL in improving perovskite passivation. These characteristics promote high PCEs of 15.1% and 21.3% for the wide‐bandgap and normal‐bandgap perovskite solar cells, respectively.